Resection of Primary Brachial Plexus Tumor via a Modified Supraclavicular Approach - Tschoe, Christine; Holsapple, James W.; Binello, Emanuela (Journal of Neurological Surgery Reports, 2014)
Benign peripheral nerve sheath tumors are generally considered curable lesions, and surgical resection is recommended as the primary line of treatment. When these tumors occur in the brachial plexus, they are most frequently accessed via the supraclavicular approach. Traditional descriptions of this approach have included either transection of sternocleidomastoid (SCM) muscle fibers or disarticulation of the clavicular head of the SCM muscle. This report presents a simple and easy-to-adapt modification of the supraclavicular approach that offers greater preservation of the SCM muscle. The modification primarily consists of the creation of an intramuscular window between the sternal and clavicular heads of the SCM via the splitting and dilation SCM muscle fibers. This technique minimizes the disruption of SCM muscle tissue compared with previous descriptions and may be associated with improved postoperative pain and return to function.
Keywords: brachial plexus tumor; supraclavicular approach; sternocleidomastoid muscle; intramuscular window